Well-being needs of elite sports coaches - Ruddock, M.; Donaldson, A. (Journal of Science and Medicine in Sport, 2024)
Introduction: The primary aim of high-performance sports coaches is to enhance and optimise the performance of athletes in competitive sport. However, they are also often responsible for: developing organizational culture; building brand awareness; representing the organisation for the media; delivering tactical and technical information; and managing a team of other high-performance coaches and support staff. Coaches in high-performance environments encounter several diverse stressors associated with their roles and responsibilities. While some coaches regularly flourish in their profession, others report fewer positive experiences. Therefore, the purpose of this research was to identify topics to include in initiatives to enhance the well-being of coaches within the Australian high-performance system. Methods: Concept mapping is a structured conceptualisation method designed to organise and represent ideas from an identified group on a topic of interest. It is a participatory mixed-methods approach that integrates qualitative individual and group processes with multivariate statistical analyses to help a group of individuals describe ideas on a specific topic and represent these ideas visually through a series of related two-dimensional maps. Eighteen coaches in the Australian high-performance system from nine different sports participated in the concept mapping activities. This included 1) brainstorming their ideas about the topics they wanted addressed or the services and programs they wanted to access through initiatives to promote coach well-being, 2) sorting the brainstormed ideas into groups based on how they thought the ideas were related to each other and 3) rating the ideas on a scale from 1 (least) to 5 (most) for how important it was that this topic or issue was included in a coach well-being initiative and how frequently coaches experienced the topic or issue. Results: Fifty-eight unique and unambiguous statements were produced by the participating coaches. Analysis of the way coaches grouped these statements together identified a 9-cluster map of topics and issues. These included (in order of relative importance rating): Knowledge sharing, career progression, job security, professional network, mental health and wellbeing, coach retention, personal development, flexible work environment and organisational support and stakeholder management. These overarching clusters of topics be considered as a representation what coaches of elite athletes wanted addressed in a wellbeing initiative. The top 20 most important statements to include in a coach wellbeing initiative were spread across all 9 clusters. The most important individual statements were: i) access to ongoing well-being support for coaches; ii) stability; avoid short term, year to year contracts and last-minute renewals; and iii) education in how to communicate effectively/with influence. Discussion: These findings represent a conceptualisation of the full range of stressors that these coaches experience. As such, these statements, when considered together, represented the lived experience of well-being needs of coaches in the Australian high-performance sport system. Impact/Application to the field: This study provides empirical evidence to inform the development of initiatives to build the individual resilience of elite sports coaches and enhance organisational support to optimise psychological well-being of high-performance coaches. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.